ChemInform Abstract: Mild Hydrothermal Crystal Growth of New Uranium(IV) Fluorides, Na3.13Mg1.43U6F30 and Na2.50Mn1.75U6F30: Structures, Optical and Magnetic Properties. Issue 22 (12th May 2016) - Yeon, Jeongho; Smith, Mark D.; Tapp, Joshua; Moeller, Angela; zur Loye, Hans‐Conrad
Abstract: Single crystals of the title compounds are hydrothermally synthesized from solutions of UO2 (OAc)2, NaF, HF, and MgCl2 or MnCl2 (autoclave, 200 °C, 1 d, ≈100% yield).